An integrated taxonomic revision of Diplotrichus (Coleoptera, Scolytinae) supports a Malagasy origin and single colonisation of South Africa - Jordal, Bjarte H. (Zootaxa, 2021)
The Afrotropical genus Diplotrichus Jordal, 2021 is revised. Altogether 21 species are included in the genus, with 10 species described as new to science: Diplotrichus pilifrons Jordal, sp. nov., Diplotrichus medius Jordal, sp. nov., and Diplotrichus calvifrons Jordal, sp. nov. from South Africa, and Diplotrichus acutior Jordal, sp. nov., Diplotrichus falcatus Jordal, sp. nov., Diplotrichus pulchellus Jordal, sp. nov., Diplotrichus granulatus Jordal, sp. nov., Diplotrichus tuberculatus Jordal, sp. nov., Diplotrichus robustus Jordal, sp. nov., and Diplotrichus plenus Jordal, sp. nov., all from Madagascar. A molecular phylogenetic analysis based on five gene fragments (COI, EF-1a, CAD, PABP1, 28S) resulted in four major clades, with South African species nested within a grade of Malagasy species, supporting a more recent colonisation of the African mainland around the early Miocene.